Road Tax on Truck Traffic with Environmental Aspects - Břetislav Andrlík (European Financial and Accounting Journal, 2014)
The contribution deals with issues of taxation of truck traffic in the Czech Republic and European Union countries. The article discusses the current need for the introduction of environmental features aiming at the mitigation of harmful substances emitted into the atmosphere to the system of truck traffic taxation. Within the tax system, we focus on the road tax mechanism, defining only those circumstances that relate to environmental features of the determination of the tax base or tax reliefs dependent on the compliance with the applicable EURO emission standard. The article outlines systems of truck taxation in the European Union member states with focus on the determination of the tax base. The EURO emission standard, which is clearly identified and binding upon all the truck producers at present, has been introduced as the environmental factor related to pollutants emitted to the atmosphere, and it subsequently assumes the role of a “green” feature of the road taxes on trucks in those EU countries which introduced such environmentally friendly aspects. A special section describes systems of road tax with environmental aspects levied on trucks in Bulgaria, Hungary, the Netherlands, Germany, Slovak Republic, Slovenia and Sweden. In conclusion, we mention the necessity of discussion over this topic in the conditions of the Czech Republic and the requirement to regulate the system of road taxes imposed on trucks, calling for reduction of harmful substances generated by traffic.
Keywords: H21; H23; 650; EURO standard; Negative externality; Road tax